2014
DOI: 10.1111/ipd.12118
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life of schoolchildren: impact of clinical and psychosocial variables

Abstract: Oral health-related quality of life was influenced by psychosocial and clinical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
87
1
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 23 publications
16
87
1
26
Order By: Relevance
“…6,7,8,12,13,14,21,24 Moreover, our results bring new evidence of the long-term effects of caries treatment on the OHRQoL of schoolchildren aged 8 to 10 years. Although other studies have demonstrated improvements in children's OHRQoL after dental treatment, they generally have focused on outcomes in younger children using the Early Childhood Oral Health Impact Scale (ECOHIS), Child-Oral Impacts on Daily Performances (Child-OIDP), the Parental-Caregivers Perception Questionnaire (P-CPQ), 17,25,26,27 and research in which treatment was proposed for early childhood caries under general anesthesia.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…6,7,8,12,13,14,21,24 Moreover, our results bring new evidence of the long-term effects of caries treatment on the OHRQoL of schoolchildren aged 8 to 10 years. Although other studies have demonstrated improvements in children's OHRQoL after dental treatment, they generally have focused on outcomes in younger children using the Early Childhood Oral Health Impact Scale (ECOHIS), Child-Oral Impacts on Daily Performances (Child-OIDP), the Parental-Caregivers Perception Questionnaire (P-CPQ), 17,25,26,27 and research in which treatment was proposed for early childhood caries under general anesthesia.…”
Section: Discussionmentioning
confidence: 57%
“…Although other studies have demonstrated improvements in children's OHRQoL after dental treatment, they generally have focused on outcomes in younger children using the Early Childhood Oral Health Impact Scale (ECOHIS), Child-Oral Impacts on Daily Performances (Child-OIDP), the Parental-Caregivers Perception Questionnaire (P-CPQ), 17,25,26,27 and research in which treatment was proposed for early childhood caries under general anesthesia. 12,28,29 In relation to CPQ instruments, Turton et al 30 evaluate the responsiveness of the Khmer version of the CPQ [11][12][13][14] in 140 children aged 8 to 14 years who received basic dental care from a local nongovernmental organization over a 6-month period. Therefore, to our knowledge, the present study is the first longitudinal study that compares the OHRQoL of children aged 8 to 10 years after caries treatment using the CPQ 8-10 over a 1 year period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentoalveolar bölgenin travmaya maruz kalması sonucunda, sert doku (dişler ve alveol kemiği) ve yumuşak dokuda (pulpa ve periodontal dokular) harabiyet oluşmakta ve nörovasküler yapıların rupturune bağlı olarak pulpada hiperemi, hemoraji, pulpal kanalda obliterasyon, nekroz, dişte mobilite, renk değişimi ve patolojik kök rezorpsiyonu gibi komplikasyonlar meydana gelmektedir. Dental travma ve sonuçları hem çocukta hem de ailesinde fiziksel, estetik ve psikolojik problemleri de beraberinde getirmektedir 5 . Süt dentisyonda oluşan travmaların daimi dentisyonu olumsuz etkileyebileceği ve genç daimi dişlerde pulpa canlılığının erken ve doğru müdahale ile sürdürülebileceği göz önünde bulundurulursa ailenin dental yaralanmalar hakkındaki bilgi düzeyi büyük önem teşkil etmektedir.…”
Section: Introductionunclassified